PENGARUH IMPLEMENTASI PROJECT BASED LEARNING BERBANTUAN MEDIA INSTAGRAM TERHADAP HASIL BELAJAR PPKN - Winda Aurin Fatakul Hidayah; Edy Herianto; Muh. Zubair; M. Ismail (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2024)
The research was conducted to find out: Is there an effect of the implementation of project-based learning assisted by Instagram media on student learning outcomes in Civics subjects at SMPN 14 Mataram. The approach used is quantitative with the type of Pre-Experimental Design using a one group pretest-postest design. The population is all VIII grade students at SMPN 14 Mataram consisting of 8 classes and the sample taken is 1 class that meets the criteria, namely class VIII A, with purposive sampling technique. Data is processed using tests. The test techniques used were pre-test and post-test. Data analysis uses prerequisite tests, namely normality test (Kolmogorov-Smirnov) and homogeneity test (Leven's statistic), and hypothesis testing using t-test (one sample t-test). The implementation of learning was carried out 4 times a meeting. There is an effect of the implementation of project-based learning assisted by Instagram media on student learning outcomes in Civics subjects. Proven by the acquisition of t- test > t table = 27.693 > 2.042